Batăvi oder Batāvi? Zu Luc. Phars. I, 430–440 - Vetushko-Kalevich, Arsenij (Hyperboreus, 2015)
One of the most serious textological issues connected with Lucan’s catalogue of Gallic tribes is the authenticity of vv. 430–440. There is no doubt that vv. 436–440 were interpolated in the Middle Ages; as for vv. 430–435, the question seems to be more intricate. There are three points making them suspicious: (1) the brevity of the second -a- in Batavi; (2) the presence of Cinga river, that actually ﬂows not in Gallia, but in the region of the Pyrenees, as Lucan well knows (cf. IV, 21); (3) the lack of direct object depending on pererrat. Batavi with -ā- is attested by Martial, Juvenal and Silius Italicus, whereas -ă-, except for Lucan, does not appear until the 6th century AD (Venantius Fortunatus). Comparison with other Gallic toponyms and ethnonyms, which occur in Lucan’s catalogue as well as by other Latin poets of the Golden and the Silver Age, demonstrates constancy of quantities. The contradiction in this case can be explained by Lucan’s unfamiliarity with the name Batavi. Such tribes as Lingones, Ruteni and Santoni, which inhabitated Gallia Celtica and were mentioned not only by Caesar, were more or less familiar to Lucan’s contemporaries and therefore less exposed to pronunciation inconsistencies. In contrast to them, Batavi, living nearly on the borders of the Roman world, are attested before Lucan only once (in a dubious passage of Caesar) and were not much talked about before the revolt of 69–70 AD. After that, since the ethnonym was frequently used, the pronunciation with -ā- was established, as can be clearly seen in the poetry of the end of the 1st century AD. Thus the essential argument against the authenticity of vv. 430–435 seems to lose its value. On the other hand, one cannot deny that the words qua Cinga pererrat gurgite remain a problem. No convincing conjectures have been proposed, but it is most probable that the passage underwent a large-scale text corruption, rather than an interpolation: unlike vv. 436–440, which are obviously inserted in order to ﬁll in the lacking areas of the Loire region, these verses do not give any reasons for interpolation.